Appraisal of hill farms in West Garo hills of MeghaJaya practising shifting cultivation, for developing optimum alternative farming system - Goswami, S N (The Indian Journal of Agricultural Sciences, 2012)
A study was conducted during 1986-87 to develop suitable optimum farm plans for 100 farms practising shifting cultivation in the Rangram block of West Garo hills district (Meghalaya) for increasing the income and employment and reducing the use of this practice. The probability proportional random sampling technique was adopted for selecting farms from the selected 5 villages. Optimum farm plans for 3 situations. viz (i) under existing resource level. (ii) under existing resource but with relaxation of working capital, and (iii) under existing resource but with simultaneous relaxation of working capital and human labour, were developed by using linear programming technique. The optimum plans developed for these situations included high-yielding varieties autumn and winter rice (Oryza stiva L.), areca nut (Areca catechu L.) and cattle (Bos indicus L.) with increase in area and number. The increase in income was 138.62, 286.80Â  and 302.64% in optimum plan I. II and III respectively compared with the existing plan Human-labour employment increased by 30.11 % in optimum plan III, whereas bullock-labour employment decreased in all the optimum plans.